Sosialisasi Sistem Informasi Manajemen Desa dengan Penerapan e-Surat Berbasis Web di Desa Sukacai Kecamatan Jiput Kabupaten Pandeglang - Ayu Mira Yunita; Agung Sugiarto; Robby Rizky; Susilawati; Zaenal Hakim; Neli Nailul Wardah (Universitas Mathla'ul Anwar Banten, 2022)
The PKM partner in this activity is Sukacai village, most of the service processes are still carried out conventionally, namely correspondence services and data processing still using a word processing program (Ms. Office), so the process takes longer to provide services and documents. less well-administered so that errors often occur and even data archives are lost or damaged because there are too many archives. There are several things that can cause problems in a system that is run manually, including the large amount of data that must be done, the complexity of the data, the limited time used to process the data. From the above problems, the community service implementing team seeks to help village officials, especially Sukacai village, in carrying out public services online and making it easier for the community to manage administration, the lecturer and student team tries to help develop the E-Letter application and to make it easier for village officials to use the application. In this e-letter, the community service implementing team conducts training or workshops on how to use this e-letter application. There are three applications of E-Letters, namely Business Certificate (SKU), Cover Letter for E-KTP, and Unmarried Statement Letter. Some of these E-letter applications are they community is facilitated by this application because the process is faster and more efficient.